Health Status of Elderly in A Rural Area of North East Region of India - Arun Ghosh; Arun Singh (Medsci Publications, 2014)
Background: The health status of elderly people is neglected in different parts of the Country. This study will reflect the condition of health status of elderly people of rural areas of remote hilly state like Tripura. Material and Methods: This is a cross sectional study of elderly people having the age 60 years. The study was carried out among the elderly people of a Bridya Ashram, named "Sandhyanir" at Gandhigram Village in a rural area of West Tripura district, 10 km from Agartala City during the year 2010-2011. Results: Out of the total 90 subjects, females are dominant having 63.33% and literacy rate among elderly males and females were 22% and 12% respectively. Peoples residing in home from different parts of district are having maximum in rural background 86.67%. All the subjects were unmarried with low economical status. 60% elderly belongs to 60-65 years of age group. 70% of total samples are having moderate disability and 93.33 % are not having any psychological distress. The commonest problems of the elderly are visual impairments, 73.33%. Hearing declination was there in 63.33%, osteoarthritis in 13%, hypertension in 53.33%, insomnia in 46.67%, RTI in 43.33%, Heartburn in 23.33%, History of operations in 10%, and Kyphosis in 6.67%. Conclusion: This cluster study gives a bird's eye view about the health status of elderly of the state. The elderly should receive the adequate medical facilities, social support and treatment irrespective to gender discrimination, financial debt and status to live an active and social productive life.